PENGARUH MOTIVASI BELAJAR DAN PERSEPSI SISWA ATAS KINERJA GURU TERHADAP HASIL BELAJAR IPAS KELAS IV DI SDN KEBON BAWANG KOMPLEK TANJUNG PRIOK - Eva Rara Puspita Agustin; Yuyun Elizabeth Patras; Tita Rosita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to investigate the influence of learning motivation and students' perceptions of teacher performance on the learning outcomes in Natural and Social Sciences (IPAS) among fourth-grade students at SDN Kebon Bawang Complex, Tanjung Priok. The research method used is quantitative, with a sample of 101 students from SDN Kebon Bawang 3 and SDN Kebon Bawang 7. Data were collected through questionnaires and analyzed using simple and multiple regression. The results showed that learning motivation has a significant positive impact on students' IPAS learning outcomes (Y = 0.336X1 + 53.380, rx1y = 0.320, r2x1y = 0.102). Additionally, students' perceptions of teacher performance also positively contribute to IPAS learning outcomes (Y = 0.340X2 + 56.694, rx2y = 0.316, r2x2y = 0.100). Together, learning motivation and students' perceptions of teacher performance have a significant impact on IPAS learning outcomes (Y = 0.308X1 + 0.310X2 + 37.361, Ry (1,2) = 0.430, R2y (1,2) = 0.185). Based on the data analysis results, it can be concluded that there is an influence of learning motivation and students' perceptions of teacher performance on the IPAS learning outcomes of fourth-grade students at SDN Kebon Bawang Complex, Tanjung Priok. These findings underscore the importance of considering learning motivation and students' perceptions of teacher performance in efforts to improve IPAS learning outcomes. The implications of this research can be used as a basis for developing more effective teaching strategies in elementary schools, particularly in the context of IPAS learning for fourth-grade students.